Enterprise Resource Planning (ERP) Performance and Hardware Requirements in Manufacturing - Andi Romansyah; Emi Sita Eriana (bit-Tech, 2025)
Despite the critical role of Enterprise Resource Planning (ERP) systems in manufacturing competitiveness, Indonesian companies frequently encounter significant performance bottlenecks attributed to suboptimal hardware configurations. Limited empirical evidence exists regarding optimal hardware specifications for ERP systems within Indonesian manufacturing contexts, creating uncertainty in technology investment decisions.This study investigates the relationship between hardware specifications and ERP system performance to develop evidence-based optimization strategies for Indonesian manufacturing companies. A mixed-methods sequential explanatory design was implemented over 18 months, examining 120 Indonesian manufacturing companies. The research employed quasi-experimental quantitative analysis combined with in-depth qualitative interviews to evaluate five critical hardware components: processor, RAM, storage media, network bandwidth, and network cards. Performance metrics included response time, transaction throughput, and system stability. The optimization framework demonstrated exceptional predictive accuracy with precision of 94.2%, recall of 91.8%, F1-score of 93.0%, and overall model accuracy of 92.5% (R² = 0.892). Hardware optimization achieved performance improvements up to 268%, with storage speed contributing 38.7%, processor performance 28.5%, and RAM capacity 19.8% to overall gains.This comprehensive framework enables Indonesian manufacturing companies to make informed hardware investment decisions with ROI achievement within 3.3 months, providing concrete guidance for digital transformation initiatives and establishing benchmarks for ERP infrastructure optimization in emerging manufacturing economies